Effect of crop intensity of soybean-cassava intercropping on storage capacity of soybean (Glycine max [L.] Merrill) seeds - Pramono Eko; Syamsoel Hadi Muhammad; Kamal Muhammad; Setiawan Kukuh (BIO Web of Conferences)
Providing of high qualified soybean seeds with minimum germination capacity of 80% to increase soybean production, apart from being largely determined by quantity of seed produced, it is also determined by its storage capacity. The aim of this research was to determine the effect of crop intensity of soybean-cassava intercropping on the storage capacity of soybean seeds, both in non-air-conditioned storage room with temperature of ±26 °C and air-conditioned storage room with temperature of ±18 °C. Six levels of crop intensity of soybean-cassava intercropping, namely 100%, 134%, 145%, 147%, 156%, and 164% were implemented in a completely randomized block design (CRBD) with 5 blocks. The sixth soybean seed lots that harvested from the different experimental plots were packed in plastic bags and stored for 10 months in that storage room. Vigor of storage capacity was measured every two months for up to 10 months. The result showed that soybean seed lots obtained from the soybean-cassava inter cropping with crop intensity of 100-164% had a similar storage capacity in air-conditioned storage room, but there was different storage capacity among the seed lots in the non-air-conditioned storage room. Storing the seed lots under temperature of ±26 °C, the storage capacity of soybean seed lot of the intercropping with crop intensity of 164% was not different from those of monocropping.